THE APPLICATION OF CONTEMPORARY DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE EDUCATION - Sagdieva Guzal Juraevna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The article examines the transformative impact of modern digital technologies on the fields of linguistics and foreign language teaching. It explores the transition from traditional methodologies to a digital-centric paradigm, highlighting the roles of corpus linguistics, Natural Language Processing (NLP), and Artificial Intelligence (AI). The paper analyzes how these tools enhance the development of the "linguistic personality" in the digital age and discusses the pedagogical shift toward personalized, technology-mediated learning environments.